Every day, chem[i]stry - Sooy, Julia (Feiwel and Friends, 2021)
"Science is all around us in our daily lives. Specifically, chemistry! When your bread toasts, when your shampoo foams, when the playground slide rusts--those are all chemical reactions. In this book, a mother and daughter experience all these things and more as they go about their day, from when they wake up, to when they go to bed."--Jacket flap.